Correlation between Family Participation in National Health Insurance and Fulfillment of Family Care Logistics in Jember Regency - Oktasari, Kingkin Nindi; Susanto, Tantut; Kurdi, Fahruddin (Al-Hijrah Indonesia, 2023)
Family participation in JKN (National Health Insurance in Indonesia) is an indicator of PIS-PK (Healthy Indonesia Program - Family Approach). JKN is also part of the National Health System (SKN) whose management consists of eight subs, one of which is management. The management theory put forward by Marquis and Huston consists of five processes, namely planning, organizing, manpower, directing, and controlling. The organizing section includes several activities, including equipment preparation and logistics. Therefore, this study intends to analyze the relationship between family participation in JKN and the fulfillment of the care logistics. This study used a correlational analysis design with a cross-sectional approach. The sampling technique used simple random sampling on 172 families. The instrument uses JKN membership and access questionnaires (Riskesdas, 2018) to measure the fulfillment of family care logistics. The results show that the fulfillment of family care logistics refers to 3 things, namely distance, time, and transportation models. Based on this, the results of the analysis of family participation in JKN with the fulfillment of family care logistics in the working area of the Sumbersari Health Center, Jember Regency, using the Chi-Square test, three references are seen, namely in terms of distance, time, and transportation models. Distance shows p-value=0.32 (>0.05), time 0.001 (<0.005), and transportation model 0.00 (<0.005). This shows that the alternative hypothesis (Ha) is accepted or that there is a relationship between the two variables. Logistics for family care in the Sumbersari Health Center, Jember Regency's working area are sufficiently fulfilled. There is a relationship between family participation in JKN and fulfillment of family care logistics in the working area of the Sumbersari Health Center, Jember Regency. The JKN participation coverage and education on the importance of participating in JKN can continue to be increased.